2022
DOI: 10.1002/ange.202116763
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Network of Crystalline Polymers for a Scalable, Nonfluorinated, Healable and Amphiphobic Solid Slippery Interface

Abstract: The fluorinated‐liquid infused amphiphobic slippery interfaces exhibiting superior sliding of the beaded oil/water droplets, often suffer from durability and contamination issues. Here, the ability of 1) hexagonal packing of hydrocarbon sides in a selected “comb‐like” polymer and 2) its reversible phase transition at 51 °C was rationally exploited to achieve temperature‐assisted rapid (<1 minute) and repetitive (50 times) self‐healable amphiphobic solid‐slippery coating on both planar and geometrically‐complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…43–47 To address this challenge, recently solid–slippery interfaces were introduced following a few approaches, i.e. , (1) infusion of phase transitioning solid lubricants (polymer and paraffin) in a porous matrix, 48–53 (2) attachment of a flexible polymer, 54–60 (3) growth of polymer brushes, 61–63 (4) layer-by-layer surface growth of nanoparticles 53,64 and deposition of nanoparticles, 65,66 and (5) assembly of oligomers. 67–70 Such earlier reported approaches mainly concentrated on minimizing the nanometric roughness to achieve sliding of beaded droplets of water and organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…43–47 To address this challenge, recently solid–slippery interfaces were introduced following a few approaches, i.e. , (1) infusion of phase transitioning solid lubricants (polymer and paraffin) in a porous matrix, 48–53 (2) attachment of a flexible polymer, 54–60 (3) growth of polymer brushes, 61–63 (4) layer-by-layer surface growth of nanoparticles 53,64 and deposition of nanoparticles, 65,66 and (5) assembly of oligomers. 67–70 Such earlier reported approaches mainly concentrated on minimizing the nanometric roughness to achieve sliding of beaded droplets of water and organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Biomimetic autocrine waxy materials (AWMs), inspired by the renewable solid epidermal waxes of terrestrial plants, are attracting increasing attention. Scientists have found that the waxy layer is an organic mixture consisting mainly of C 20 -C 34 aliphatic substances , and usually exhibits hydrophobic properties. , By mimicking the waxy layer in leaves, Wang et al reported a solid organogel material with a regenerable sacrificial alkane surface layer and demonstrated an important role in combating solid deposition . Some scholars have exploited the rapid autocrine ability and hydrophobicity of AWMs, and the as-prepared materials quickly and spontaneously recovered their superhydrophobicity even after being subjected to severe plasma etching .…”
Section: Introductionmentioning
confidence: 99%